2013
DOI: 10.1002/14651858.cd003588.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing for intravascular administration set replacement

Abstract: Issue 9. Cochrane Reviews are regularly updated as new evidence emerges and in response to comments and criticisms, and the Cochrane Database of Systematic Reviews should be consulted for the most recent version of the Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 42 publications
2
28
0
3
Order By: Relevance
“…The variability in recommendations has implications for hospital policy developers and may create confusion and uncertainty for nurses. The most recent Cochrane review (Ullman et al, ) found no evidence of a difference in catheter‐related or infusate‐related bacteraemia or fungaemia between different frequencies of administration set replacement (24, 48, 72 or >96 hr).…”
Section: Introductionmentioning
confidence: 99%
“…The variability in recommendations has implications for hospital policy developers and may create confusion and uncertainty for nurses. The most recent Cochrane review (Ullman et al, ) found no evidence of a difference in catheter‐related or infusate‐related bacteraemia or fungaemia between different frequencies of administration set replacement (24, 48, 72 or >96 hr).…”
Section: Introductionmentioning
confidence: 99%
“…The child’s case study, in agreement with previous literature,2 3 has demonstrated that the harm associated with CVADs frequently occurs during the later stages of CVAD dwell, not on the early days after insertion. Paediatric CVAD maintenance procedures such as flushing,20 dressing,21 administration set changes,22 and hub decontamination23 are not well supported by evidence, likely perpetuating these preventable complications for patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies indicate that the routine replacement of PIVCs (using predetermined time frames, e.g. 72-96 h) does not show advantages when compared to clinically indicated replacements [44][45][46]. Previous to the administration of the intravenous medication, vein permeability will be assessed and the pulsatile (push-pause) delivery action will be used to optimize flush outcomes and minimize damage to the vein [31,33,36].…”
Section: Interventionsmentioning
confidence: 99%